The Birds of Opulence - Wilkinson, Crystal (Book collections on Project MUSE., 2016)
A lyrical exploration of love and loss, this book centers on several generations of women in a bucolic southern Black township as they live with and sometimes surrender to madness. The Goode-Brown family, led by matriarch and pillar of the community Minnie Mae, is plagued by old secrets and embarrassment over mental illness and illegitimacy. Meanwhile, single mother Francine Clark is haunted by her dead, lightning-struck husband and forced to fight against both the moral judgment of the community and her own rebellious daughter, Mona. The residents of Opulence struggle with vexing relationships to the land, to one another, and to their own sexuality. As the members of the youngest generation watch their mothers and grandmothers pass away, they live with the fear of going mad themselves and must fight to survive. The author offers up Opulence and its people in lush, poetic detail. It is a world of magic, conjuring, signs, and spells, but also of harsh realities that only love - and love that's handed down - can conquer.